Status Mutu Kualitas Udara Ambien Pada Beberapa Kota Besar di Papua Menggunakan ArcGIS - Indah D. Setyowati; Auldry F. Walukow; Basa T. Rumahorbo; Johnson Siallagan; Novita Medyati (Jurnal Biologi Papua, 2023)
The increase in population in recent years has affected the utilization of facilities and infrastructure, including the use of vehicles. For the past 10 years, the population in Papua has increased by around 4.13% per year, resulting in the need for daily mobility to increase. The high mobility demand in Papua could affect the increase in pollution, thus affecting the air quality. Exposure to pollutants in ambient air and environmental noise in the long term will have an impact on human health. Therefore, in this study, we analyze the current conditions of air pollution parameters in several major cities in Papua, such as Jayapura, Merauke, Sentani, and Timika. The method used is a survey. Environmental parameters measured were air content of SO2, NO3, PM 10, PM 2.5, HC, O3, CO, dust, Pb, noise, and The Air Pollutant Standard Index (ISPU) value. Observational data obtained were analyzed and displayed using the ArcGIS program. The parameters for determining the location of sampling points are densely packed highway areas, industrial areas, residential areas, and offices. The results of the study indicated that the ambient air quality in all study sites is below the required quality standard. While the results of environmental noise that exceed the highest quality standards located in specifics area on each study site are as follows, Merauke at PLTD Merauke I PT. PLN Persero with 81.24 dB(A), Sentani at Sentani City Square Roads with 70.2 dB (A), Mimika at Perumahan Pemda SP-2 with 65.30 dB(A), and Sentani at Kantor Bupati Jayapura with 64, 54 dB (A). However, the ISPU value for pollutant substances is still in the range of 0-50, which means that the air quality category is very good to carry any outdoor activities, and does not have any negative impact on humans, animals, or plants.Key words: air quality; noice; ISPU; Papua.